Overview of Role-Playing Techniques in Group Guidance Services to Improve Students’ Interpersonal Intelligence - Dwiana Pratiwi; Mustapha Qureshi; Yassine Mohamed; Mounika Ardchir (International Journal of Research in Counseling, 2022)
Some students still have low interpersonal intelligence, so students have difficulties in their social relationships. It aims to reveal the effectiveness of role-playing techniques in group guidance services to improve students' interpersonal intelligence. The research method uses a quantitative approach, in particular experimental. To obtain data using the student's interpersonal intelligence questionnaire. The data were analyzed using a paired t test, because the study involved only one group of respondents. The results revealed that role playing techniques in group guidance services are effective in improving students' interpersonal intelligence. The results of the study are expected to be used by BK teachers in schools to improve students' interpersonal intelligence. It is also expected to be used by subsequent researchers to utilize role playing techniques in group guidance to improve other psychological aspects.